The mechanism of anticarcinogenic effects of tualang honey (TH) on induced breast cancer in rats - Ahmed, Sarfraz (2015)
The multifloral Tualang honey (TH) and the monofloral Manuka honey (MH) have been reported to have antimicrobial, anti-inflammatory, antioxidant and anticancer effects. Unlike the Manuka honey, TH is not extensively studied. We conducted a study to evaluate the mechanisms of the preventive and therapeutic effects of TH and MH on experimental breast cancer induced rats using carcinogen 1-methyl-1-nitrosourea (MNU). We also conducted a similar cancer therapeutic study using Honey sugars analogue (HSA), a fluid which contains the proportion of sugars in honey. A total of 130 female Sprague-Dawley rats were used. Sixty female rats were randomly divided into 6 groups with 10 animals per group in each study. Group ‘0’ did not receive MNU and did not receive honey (negative Control); Group 1 received MNU but not honey/honey sugars analogue (positive Control). Groups 2, 3 and 4 were fed orally with 0.2, 1.0, 2.0, 1.0 g/kg body weight of TH, and Group 5 received 1.0 g/kg body weight of MH. Group 6 received 1.0 g/kg body weight of HSA in therapeutic study. For the “cancer-preventive” study, honey was given one week prior to MNU-induction and for the “cancer-therapeutic” study; honey was given when the first palpable tumor reached 10-12 mm in size. The development of mammary tumors and body weights were charted throughout the study. The rats in all treated groups continued to receive the treatment until the 120th day when they were sacrificed. At autopsy, blood was drawn for haematological and serological analysis. The tumors were harvested for gross and histopathological examinations, and determination of pro and antiapoptotic proteins expression by immunohistochemistry using a panel of antibodies. Results showed that TH and MH treated rats of “cancer-preventive” groups had a lower tumor incidence (the number of animals developing tumors), and a longer latency period (the interval when the first tumor developed after MNU induction) compared to the non-treated control group. The number of tumors developed in the treated groups was lesser than the non-treated control group (p˂0.05). Regardless of honey treatment given, either before or after the breast cancer development, the tumors had slower size increment (˂1.48 cm3 and ˂2 cm3 for cancer preventive and therapeutic effects respectively) compared to the non-treated control group (=2.85 cm3 and =3.84 cm3 respectively). The median weight (g) and size (cm3) of the tumors in treated groups were also significantly lower (p˂0.05). A significant actual body weight gain was Histopathological examination showed various tumor patterns; ranging from benign, DCIS (ductal carcinoma in situ), micropapillary and NOS (not-otherwise specified) type. The treated groups showed more patterns of benign tumors compared to the non-treated control group. The majority of the tumors in the treated groups were of better grade (grade І and ІІ) compared to the non-treated control group (grade ІІІ). The haematological parameters showed that different dosages of TH, MH and HSA had an increasing effect on Hb (haemoglobin), RBC (red blood cells), PCV (packed cell volume), MCV (mean corpuscular volume), lymphocytes and eosinophils counts compared to the non-treated positive control. Treatments with TH, MH and HSA presented a decreasing effect on TWBC (total white blood cells), RDW (red cell distribution width), polymorphs, monocytes and platelets counts compared to the non-treated positive control. Various preparations of TH, MH and HSA showed no hyperglycemic effect on fasting blood glucose level. Serum biochemistry showed that the rats treated with TH, MH and HSA had an increased level of pro-apoptotic proteins; Apaf-1 (apoptotic protease activating factor 1) and IFN-